FACTORS ASSOCIATED WITH TB/HIV CO-INFECTION AMONG DRUG SENSITIVE TUBERCULOSIS PATIENTS MANAGED IN A SECONDARY HEALTH FACILITY IN LAGOS, NIGERIA - Adejumo, Olusola A.; Daniel, Olusoji J.; Otesanya, Andrew F.; Adegbola, Adebukola A.; Femi- Adebayo, Temitope; Bowale, Abimbola; Adesola, Sunday; Kuku, Olugbenga O.; Otemuyiwa, Kehinde O.; Oladega, Shafaatu N.; Johnson, Eze O.; Falana, Ayodeji A.; et al. (African Journal of Infectious Diseases (AJID), 2017)
Background: This study assessed factors associated with TB/HIV co-infection among TB patients managed in a secondary health facility in Lagos Nigeria. Materials and Methods: A retrospective review of treatment cards of patients seen at a secondary referral hospital between January 1 2014 and December 31 2014 was conducted. Treatment outcomes and factors associated with TB/HIV co-infection were assessed. Results: Of the 334 records of patients reviewed, the proportion of patients with TB/HIV co-infection was 21.6%. The odds of having TB/HIV co-infection was 2.7 times higher among patients above 40 years than patients less than 25 years (AOR 2.7 95% CI 1.1 – 6.5, p =0.030). In addition, the odds of having TB/HIV co-infection was 3.3 higher among extrapulmonary TB cases (AOR 3.3; 95% CI 1.2 – 9.5; p = 0.026) and 2.1 times higher among retreated patients (AOR 2.1; 95% CI 1.1 – 3.9; p = 0.017) than pulmonary TB and new patients respectively. The chance of having TB/HIV co-infection was 2.7-fold more in patients with poor treatment outcomes than patients with treatment success (AOR 2.7; 95%CI 1.3 – 5.4; p =0.006). Conclusion: TB/HIV co-infection rate was high in the study area. There is need to put measures in place to improve treatment outcomes of TB/HIV co-infected patients.